The Effect of Physical and Mental Practice on Motor Learning of Educable Mentally Retarded Students - Rasoul Hemayat talab; Ahmad Reza Movahedi (University of Tehran, 2009)
The Purpose of this study was to compare the effects of different combinations of mental and physical practices on the acquisition and retention of a motor skill in mentally retarded male students. Subjects were 40 guidance students who were healthy and novice in basketball penalty shot. They were selected randomly and were assigned to 5 homogeneous groups (4 as experimental and 1 as control) based on their pretest scores, IQ and their ability in mental imagery. They exercised for 8 weeks, 3 sessions per week. Kolmogorov-Smirnov test, paired T test, one-way ANOVA and Tukey post hoc test were used to analyze the data. It was observed that all four variations of practice improved their performance, yet the mental practice followed by physical practice group outperformed the other groups. The results suggest that mental practice followed by physical practice results in an outstanding performance in mentally retarded adolescents.